THE EFFECT OF DRUM SPEED ON TIME AND GRAIN SIZE RESULTS FROM THE MILLING PROCESS - Sepriadi Sepriadi; Isdaryanto Iskandar; M. Ari Wijaya (Bajang Institute, 2022)
Grinding/crushing is a process of reducing the size in a crushing plant to get the desired size. The coal ball mill technique is where the ball collides with the feed on the tube wall, thus cracks will form in the feed which will result in a smaller size. Limitation of the problem in this study is the effect of speed on time and grain size resulting from the milling process, the mass of the sample used is 500 grams with grain sizes that do not pass a 10 mesh sieve, there are three types of pulley variations, namely, pulleys of 2 inch, 4 inch. , and 20 inches with a ball as a control using 10 uniform balls with a diameter of 4.58 cm